Perbedaan Pengaruh Progressive Muscular Relaxation dan Senam Yoga terhadap Penurunan Hipertensi pada Lansia di Desa Tohudan, Colomadu, Karanganyar - Windiastoni, Yoga Handita; Basuki, Nur; Haritsah, Nurul Fithriati (Jurnal Terapi Wicara dan Bahasa, 2025)
Background: Hypertension or high blood pressure is a condition where a person's blood pressure is at 130/80 mmHg or more. Hypertension can also be called a silent killer disease, meaning that this disease often occurs without any complaints and signs that appear beforehand (WHO 2018). If this hypertension is left untreated, it can cause complications such as heart disease, kidney disease, and stroke. The estimated number of people with hypertension in Indonesia is 63,309,620 people, and the death rate from hypertension is 427,218. In Indonesia, hypertension that occurs in the 31-44 age group is 31.6%, 45-54 years old 45.3%, 55-64 years old 55.2% Therefore, hypertension cannot be underestimated (Riskesdas, 2018). Objectives: (1) to determine the effect of yoga on reducing blood pressure in elderly people with hypertension, (2) to determine the effect of progressive muscular relaxation on reducing blood pressure in elderly people with hypertension, (3) to determine whether there is a difference in the effect between yoga and progressive muscular relaxation on reducing blood pressure in elderly people with hypertension, (4) to determine which has a greater effect between yoga and progressive muscular relaxation on reducing blood pressure in elderly people with hypertension. Methods: This study is an experimental study, using a two group pre-test and post-test design involving 20 subjects who were randomly divided into 2 groups. Group I was given progressive muscular relaxation treatment and group II was given yoga treatment. With a frequency of exercise once a week for 3 weeks. The measuring instrument in this study used a sphygmomanometer. Results: Hypothesis I test using paired sample t-test obtained a p value: 0.000 (p <0.05) while hypothesis II test using paired sample t-test obtained a p value: 0.000 (p <0.005) for hypothesis III test using independent sample t-test obtained a p value: 0.042 (p <0.005). Conclusion: (1) there is an effect of yoga on reducing blood pressure in elderly people with hypertension, (2) there is an effect of progressive muscular relaxation on reducing blood pressure in elderly people with hypertension, (3) to find out whether there is a difference in the effect between yoga and progressive muscular relaxation on reducing blood pressure in elderly people with hypertension, (4) yoga has a greater effect than progressive muscular relaxation on reducing blood pressure in elderly people with hypertension. Keywords : Yoga, Progressive Muscular Relaxation, Hypertension, Elderly